Explaining How cognitive behavioral approaches work for low back pain: Mediation analysis of the back skills training trial - Fordham, B; Ji, C; Hansen, Z; Lall, R; Lamb, SE (Lippincott, Williams & Wilkins, 2017)
Study Design: This is secondary research examining the longitudinal mediation effect within a structural equation model.